Mythologic Spectrum Of “the Calling Of The Godess” Of Grigol Robakidze - Nikoleishvili, Avtandil (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Due to the fact that majority of Grigol Robakidze’s (1880-1962) works made in emigration time are written in German. Georgian readers and specialists had just general understanding till present time. This part of the creative inheritance of the writer is not studied properly. Fortunately, this unwanted condition has essentially changed recently and today the Georgian translations of Grigol Robakidze famous works are widely available for readers. Despite living in emigration, the main source of his literary inspiration was again the creative description of the problems of Georgia and Georgian people, he was devoted to old artistic-aesthetic outlooks and principles. In the creations of emigrant period mythological indices, romantic reflections of ancient folk stories and Georgian customs and traditions take the major part. From this point of view his novel “Goddess calling” (1934) is especially interesting. It can be considered as an extension of Georgian, in particular Svanetian folkmythological faith. Description of exotic events, completely unknown to the foreign reader, with high lexical art gives much more impression to the novel.